Information Technology Innovation for Mosque Management with Digital Solutions - Marjito Marjito; Jajat Sudrajat; Dheni Apriantsani Budiman; Isbandi Isbandi; Isak Ramlan (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2024)
The community service team of faculty members and students from STMIK Mardira Indonesia has executed a project to manage activities and finances at Al-Muhajirin Cijerah Mosque. The team concentrated on creating a web application that incorporates essential elements, like a login page, dashboard, financial data, and a Friday prayer schedule. The primary objective of this project is to improve efficiency and transparency in the management of mosques, namely for the Mosque Management Committee. The approach entails advancing information technology and training mosque managers to optimize the application’s use. The result of this project is the effective execution of the Mosque Activities and Financial Management Website Application. This tool enables mosque managers to manage daily operations and oversee financial matters more efficiently. This community service initiative has substantially enhanced the management of Al-Muhajirin Cijerah Mosque by implementing information technology. It is anticipated that these measures can be enhanced and persist in delivering sustainable advantages for the mosque and its community.